NSW Water Police boat Vanguard, Sydney Harbour, Sydney 2000 Olympic Games, 24 September 2000 [2] - Seselja, Loui, 1948- (2000)
The Vanguard policed Sydney Harbour during the Olympics.
Title from the descriptive list.
Marathon, sailing and athletics events, Sydney 2000 Olympic Games, 24 September 2000.
Also available online
Keywords: Sailing -- Competitions -- New South Wales -- Sydney -- Photographs